Consolidated Reading Strategies Used in Comprehending Text from Various Studies: A Systematic Literature Review - John Rey Osben Pelila; Amabel C. Palangyos (Halu Oleo University, 2021)
A number of studies about reading strategies conducted before 2020 have mostly identified respondents' strategies and the significant relationship of such reading strategies with different factors or variables. However, only a few tried to gather and list the plethora of reading strategies of different studies. Hence, the present study aimed to identify the most focused studies in reading strategies and consolidate all the most mentioned reading strategies from various studies. A systematic literature review was employed in the present study. Also, the researchers generated literature in Ebscohost and ERIC databases. Through inclusion-exclusion criteria, 41 articles (27- Quantitative; 5 Qualitative; 9-Mixed-method) were included for synthesis. It was found out that most research in 2020 and beyond still focused on identifying the reading strategies of their respondents and looking for the relationship of reading strategies in different factors. On the other hand, 71 reading strategies (13- before-reading, 44- while reading, 14- postreading) were consolidated based on the computed frequency and percentage. As suggested, these reading strategies can aid the reading activities of readers, especially that most learnings are in the online phase.